KIPRAH ULAMA PEREMPUAN DI KOTA BANJARMASIN, KOTA BANJARBARU DAN KABUPATEN TAPIN: ANALISIS FILSAFAT FEMINISME PROFETIK - Kumari, Fatrawati; Kurdi, Muqarramah Sulaiman; Syafi’i, Muhammad (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2024)
This study investigates the roles and contributions of female scholars (ulama) in South Kalimantan, specifically in the cities of Banjarmasin, Banjarbaru, and the Tapin district, through the lens of prophetic feminism. The research employs a qualitative field study approach, gathering data through interviews, observations, and document analysis. The results highlight the profound impact these female scholars have had in religious education, social initiatives, and organizational involvement. By integrating the three main principles of prophetic feminism—structural-transcendental epistemology, the concept of worship within feminist movements, and the interconnection of divine and human consciousness—the study reveals how these scholars bridge theoretical and practical aspects of feminism within their communities. The findings underscore the importance of recognizing and documenting the contributions of female scholars as part of Islamic heritage, advocating for gender equality through education, and fostering a more just and harmonious society through actions rooted in compassion and wisdom..